(untitled) (Journal of International Studies, 2020)
Although Malaysia established official diplomatic relations with Myanmar (formerly Burma) in 1958, it may, however, appear that the former only started paying attention toits relations with the latter since 1988, especially when Myanmar ended its almost threedecades of self-imposed isolation. Contrary to this, Malaysia in fact has had a longhistory of close and cordial relations with Myanmar since 1958, although there wereperiods when relations between both took a downside. While Malaysia’s relations withMyanmar can be categorised as close and cordial in the 1950s and 1960s, it however,became low key in the late-1970s and early 1980s. Nevertheless, from the late-1980s onwards, Malaysia-Myanmar relations once again rose to a significant level, especially during the administration of Tun Dr. Mahathir Mohamad (1981-2003). From available evidence, it appears that Malaysia’s relations with Myanmar were very much "personalised", often centered on the leaders of both countries. In another direction and inspite of the existence of fraternal relations between leaders of both states, it can be noticed that Malaysia’s stance towards Myanmar has been riddled with inconsistencies and contradictions. This has been evident since 1988 when Malaysia has practiced a rather contradictory policy especially when it concerns Myanmar’s slow pace of political reform and its abysmal human rights record. This is because while Malaysia has, on occasions, criticised Myanmar for its human rights violations, at the same time it has often back-tracked from its earlier pronouncements. In this connection, this paper attempts to discuss and analyse the factors that have influenced and shaped Malaysia’S relations with Myanmar since 1958. The paper will be divided into three major periods namely the pre-1988 period, relations from 1988 till 2003, and finally, relations since 2004. This is because while Malaysia had little economic interests in Myanmar in the pre-1988 period, its investments has grown since 1988, with economic priorities becoming the major driving force in its relations with the latter. Apart from that, Myanmar’s self-imposed policy of isolation that was eventually aborted in 1988 too had its bearings on the reiations between both countries. Not only did Myanmar remain relatively isolated on the one hand, Malaysia too had little interest in the latter, on the other.